2017
DOI: 10.1016/j.hpb.2017.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive pancreatoduodenectomy

Abstract: MIPD appears to provide similar perioperative and oncologic outcomes in selected patients, when performed at experienced, high-volume centers. Its overall role in pancreatoduodenectomy needs to be better defined. Improved training opportunities, registry participation and prospective evaluation are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 42 publications
2
44
0
1
Order By: Relevance
“…5 In terms of oncological outcomes, the current study showed no significant differences between LAPD and OPD with regards to number of lymph nodes retrieved and margin status, a finding that was in line with existing studies. The current matched study revealed lower respiratory complications and faster time to ambulation in the LAPD group, while existing analyses report a shorter hospital stay in MIPD as compared to OPD.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…5 In terms of oncological outcomes, the current study showed no significant differences between LAPD and OPD with regards to number of lymph nodes retrieved and margin status, a finding that was in line with existing studies. The current matched study revealed lower respiratory complications and faster time to ambulation in the LAPD group, while existing analyses report a shorter hospital stay in MIPD as compared to OPD.…”
Section: Discussionsupporting
confidence: 91%
“…While minimally invasive pancreatic surgery is still not widely adopted, there are suggestions that similar advantages from laparoscopy seen in the other fields of general surgery can be conferred to pancreatic operations, possibly improving its morbidity rates. 5 While this could be partially attributed to smaller tumours selected for MIPD, the better visualization of blood vessels via the MIPD camera platform could possibly have allowed for improved surgical haemostasis. 20 Nevertheless, these studies remain retrospective in nature and the Dutch LEOPARD-1 21 and Swedish LAPOP (http://www.isrctn.com/ISRCTN26912858 estimated completion date in 2020) randomized controlled trials should provide a better platform for comparison between both modes of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations